Nikolai Rimsky-Korsakov's use of the byliny (Russian oral epic narratives) in his opera Sadko - Reeve, Brian (2005)
This thesis analyses the background in folk music, folk literature and folk art of Rimsky-Korsakov's sixth opera Sadko (1897). Attention is especially focused on the folk genre of the bylina, or Russian legendary and mythical oral epic narrative, from the field of which, uniquely in Russian opera, the plot of the opera is drawn. Furthermore, many incidental details of libretto and staging are derived from these epics, and, too, lengthy vocal extracts declaimed in the style of a typical Russian peasant bard. Rimsky-Korsakov also drew, however, on many other genres of folk music and folk art for his opera, and this thesis demonstrates that there is hardly one detail of this work, including cast list and stage directions, which does not derive from the Russian folk tradition. However, some critics have maintained that the measured oral unfolding of an epic narrative does not lend itself readily to adaptation for the stage, and that there are long periods of stasis in the action of the opera. The thesis rebuts this assertion by examining Rimsky-Korsakov's artistic and aesthetic conceptions, and by demonstrating that, through his adaptation of such epic material for the musical theatre, the composer was attempting to create a new genre of stage art, in which the conventional dramatic canons were to be set aside. This thesis, therefore, firstly analyses the genre of the bylina in detail, then studies Rimsky-Korsakov's background in the culture of his period, which led to his profound immersion in Russian folk culture. Subsequent to this, the other major sources of the opera Sadko are examined, as are Rimsky-Korsakov's collaboration with Mamontov's Private Opera Company, which premiered this work, owing to the composer's difficulties with the Imperial Theatres. Following an analysis of the score and libretto to ascertain how the composer incorporated his sources into his work, the thesis concludes with an evaluation of the alleged dramatic weakness and static quality of the score, and an analysis of whether the attempt to transfer an oral linear narrative to the stage was in fact successful.